2017
DOI: 10.1007/s00709-017-1101-4
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic acid modulates antioxidant defense systems and mitigates drought-induced damage in Kentucky bluegrass seedlings

Abstract: Drought stress occurs frequently and severely as a result of global climate change, and it exerts serious effects on plants. 5-Aminolevulinic acid (5-ALA) plays a crucial role in conferring abiotic stress tolerance in plants. To enhance the drought tolerance of turfgrass and investigate the effects of 5-ALA on antioxidant metabolism and gene expression under drought stress conditions, exogenous 5-ALA was applied by foliar spraying before Kentucky bluegrass (Poa pratensis L.) seedlings were exposed to drought [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…The promotive effect of ALA on plant drought tolerance was first reported in wheat (Al‐Thabet ) and barley (Al‐Khateeb ), and then tobacco (Cheng et al ). Thereafter, ALA‐promoted drought tolerance of Glycyrrhiza uralensis (Zhang et al ), Sarcandra glabra (Zhang et al ), Fagopyrum dibotrys (Wei et al ), Banana (He et al ), Brassica napus (Liu et al ), Dalbergia odorifera (Wang et al ), Leymus chinensis (Song et al ) and Poa pratensis (Niu et al ) were successively reported. However, this effect of ALA is still very mystery because many studies have shown that ALA promotes leaf stomatal opening and increases transpiration (Wang et al ; Chen et al ; An et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The promotive effect of ALA on plant drought tolerance was first reported in wheat (Al‐Thabet ) and barley (Al‐Khateeb ), and then tobacco (Cheng et al ). Thereafter, ALA‐promoted drought tolerance of Glycyrrhiza uralensis (Zhang et al ), Sarcandra glabra (Zhang et al ), Fagopyrum dibotrys (Wei et al ), Banana (He et al ), Brassica napus (Liu et al ), Dalbergia odorifera (Wang et al ), Leymus chinensis (Song et al ) and Poa pratensis (Niu et al ) were successively reported. However, this effect of ALA is still very mystery because many studies have shown that ALA promotes leaf stomatal opening and increases transpiration (Wang et al ; Chen et al ; An et al ).…”
Section: Discussionmentioning
confidence: 99%
“…5‐aminolevulinic acid (ALA) is a key precursor in tetrapyrrole biosynthesis in all organisms, such as chlorophyll and heme in plants. It has been recognized as a vital plant growth regulator due to its various roles in several key physiological processes such as promoting plant growth and conferring abiotic stress tolerance in plants (Liu et al , Xu et al , Niu et al , Sun et al , Akram et al , Liu et al , Wu et al ). Increasing attention has been paid to ALA because of its environmental‐friendly characteristic and great application potential in agriculture (Wang et al , Akram and Ashraf ) and horticulture (Feng et al , An et al , Zheng et al , An et al , Zheng et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Introduction 5-aminolevulinic acid (ALA) is a key precursor in tetrapyrrole biosynthesis in all organisms, such as chlorophyll and heme in plants. It has been recognized as a vital plant growth regulator due to its various roles in several key physiological processes such as promoting plant growth and conferring abiotic stress tolerance in plants , Niu et al 2017, Sun et al 2017, Akram et al 2018, Liu et al 2018, Wu et al 2018. Increasing attention has been paid to ALA because of its environmental-friendly Abbreviations -ABA, abscisic acid; ALA, 5-aminolevulinic acid; AsA, ascorbic acid; BR, brassinosteroid; CalA, calyculin A; CAT, catalase; DPI, diphenylene iodonium; GFP-TUA6, green fluorescent protein-tagged -tubulin 6 transgenic Arabidopsis; H 2 O 2 , hydrogen peroxide; MeJA, methyl jasmonate; MS, Murashige and Skoog; MTs, microtubules; OA, okadaic acid; OE, overexpression; PP2A, type 2A protein phosphatase; PP2A-C2, C2 subunit of type 2A protein phosphatase; PP2A-C2-OE, PP2A-C2 overexpression; PPFD, photosynthetic photo flux density; ROS, reactive oxygen species; VBT, vinblastine. characteristic and great application potential in agriculture (Wang et al 2003, Akram andAshraf 2013) and horticulture (Feng et al 2016, An et al 2016b, Zheng et al 2017, Zheng et al 2018.…”
mentioning
confidence: 99%
“…Puyang et al (2015) reported high degradation of the chloroplast after ROS generation, which was attributed to the chloroplast being the principal site of ROS production. Niu et al (2017) reported the production of MDA, formed from lipid oxidation, as an indication of cell membrane damage due to ROS accumulation.…”
Section: Introductionmentioning
confidence: 99%